Bibliographic analysis of p53-gene family and gene sequence analysis of p73 in colorectal carcinoma. - Brennan, Tang Yet Shen (Universiti Malaysia Sarawak (UNIMAS), 2022)
Colorectal carcinoma (CRC) is one of the leading causes of cancer deaths yearly. Lately, there has been an influx of information regarding the p53-gene family in colorectal carcinoma in the form of publications. Therefore, there is a need to access and quantitatively analyze these publications in detail to obtain the parameters and trend of this topic of research. This information is said to be the key to various cancer treatments and act as a platform to frame future policies regarding cancer. Previous studies have also shown that mutations in the p73 gene have limited adverse effects leading to colorectal cancer. Bibliographic analysis of the p53-gene family was done using RStudio on the Scopus database to analyse this information by observing the parameters and trend of this topic of research throughout the years to predict its development. This study focused on accessing the parameters and trends of publications pertaining to the p53-gene family as well as to investigate the correlation between mutations in the p73 gene with colorectal cancer through comparative gene sequence analysis. Publications from the year 2010 to 2021 were used for the bibliographic analysis. The number of publications on the p53-gene family in colorectal cancer were found to be steadily increasing with China having the highest number of international collaborations at 534. In comparative gene sequence analysis, HT29 and HCT116 cell lines were used where the p73 gene were sequenced and compared with the wild type. There was limited correlation found between mutations of the p73 gene with the development of colorectal carcinoma.